Medical and care compunetics 2 - Bos, Lodewijk; Laxminarayan, Swamy; Marsh, Andy (Studies in health technology and informatics ;, 2005)
The International Council on Medical and Care Compunetics (ICMCC) was founded in 2004 to create the infrastructure necessary for business-to- business and business-to-customer applications of information and communication technology in the medical and care domains. This text features a collection of papers delivered at ICMCC symposia in 2005. Follo.